2020
DOI: 10.21203/rs.3.rs-23027/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health-seeking behavior of patients with COVID-19 infection

Abstract: Background: Corona Virus Disease 2019 (COVID-19) emerged across the world, and the disease course can be affected by health-seeking behavior of patients. This study aimed to explore the influence of the health-seeking behavior of patients with COVID-19 on disease process. Methods:A retrospective study was conducted to analyze the health-seeking behavior of discharged patients with COVID-19 infection. Patients were categorized into three groups based on the times of visiting hospital, and the Mann-Whitney U and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…A total of 125 participants' health-seeking behaviours, among those who tested positive for COVID-19, were impacted by the pandemic in the current study. This is comparable to the study by Tian et al, which found that patients' health-seeking behaviours were greatly impacted by their prior interactions with COVID-19 patients [ 17 ]. These patients continue to experience significant physical and psychological problems even after being discharged.…”
Section: Discussionsupporting
confidence: 87%
“…A total of 125 participants' health-seeking behaviours, among those who tested positive for COVID-19, were impacted by the pandemic in the current study. This is comparable to the study by Tian et al, which found that patients' health-seeking behaviours were greatly impacted by their prior interactions with COVID-19 patients [ 17 ]. These patients continue to experience significant physical and psychological problems even after being discharged.…”
Section: Discussionsupporting
confidence: 87%
“…in Beijing, China. [ 17 ] The reason for less time taken for seeking treatment can be attributed to increase sensitization of people regarding COVID-19 by that point of time in India. Confirmation of diagnosis is most important milestone for isolation and treatment of patient.…”
Section: Discussionmentioning
confidence: 99%
“…Like other epidemic diseases, people expect to know what measures can be taken to prevent and treat this virus. Since no specific control has yet been discovered for the prevention and treatment of this disease, early diagnosis and rapid treatment of this disease is necessary because not only does the patient become involved in the disease, but also the risk of infection transmission and disease outbreak significantly can increase (2). Therefore, the need for selfcare and self-control to preclude the prevalence of this disease is of great importance.…”
Section: Contextmentioning
confidence: 99%